Exclusive use of different types of tobacco products, exposure to secondhand tobacco smoke and risk of subtypes of head and neck cancer among Indian males. Issue 3 (8th September 2022) - Gholap, Devyani; Dikshit, Rajesh; Chaturvedi, Pankaj; Chaturvedi, Anil K.; Manjrekar, Ankita; Mhatre, Sharayu
Abstract: Tobacco products are used in vary many forms in India. Although the risk of tobacco uses in developing head and neck cancer (HNC) is known, risk by exclusive use of different tobacco products on HNC and its subtypes is poorly understood. A case‐control study was conducted at a tertiary cancer hospital, which receives cases from different geographical regions of India with use of different types of tobacco products. The study included 824 oral cavity (OC), 149 oropharynx (OPX) 104 hypopharyngeal (HPX) and 81 larynx (LX) cancer cases and 1206 visitor controls. Information on 11 different types of tobacco products and exposure to secondhand smoke was collected through structured questionnaires. Odds ratios (OR) and 95% confidence intervals (CI), for the association of various HNC subtypes with exclusive use of each tobacco product compared to nonusers of tobacco were estimated using logistic regression models, after adjusting for potential confounders. Exclusive use of any type of smokeless tobacco product was strongly associated with all subtypes of HNC. Gutka chewing (only) had highest risk (OR = 33.67; 95% CI = 19.8‐57.0) while exclusive users of betel quid with tobacco (BQ + T), tobacco quid, Khaini, Mawa and Mishri users had a OR of 14.77, 24.20, 5.33, 2.96 and 3.32, respectively, for development of OC. Bidi smoking and secondhand smoke was independently associated with increased risk of HNC. Our study indicates that tobacco control policies should focus on product specific awareness messaging that switching between tobacco product types is not a safe alternative to complete cessation. Abstract : What's new? While overall tobacco use increases head and neck cancer (HNC) risk, specific risks associated with exclusive use of individual tobacco products remain unclear. In our study, different smokeless and smoked tobacco products and secondhand smoke exposure were investigated for individual impacts on HNC risk in patients in India. Analyses show that risk of all HNC subtypes is increased by exclusive use of any smokeless tobacco product. Gutka chewing poses the greatest risk. HNC risk is also independently associated with bidi smoking and secondhand smoke exposure. The findings indicate that different tobacco products, regardless of method of consumption, increase HNC risk.